The Position of Substitute Heirs as Perpetrators of The Murder of Direct Heirs Based on Civil Inheritance Law - Aulyanti, Davina Dewi; Taupiqqurrahman (Universitas Medan Area, 2024)
This article aims to examine the position of a substitute heir who has killed a direct heir, based on Civil Inheritance Law, and analyze specific conditions under which the substitute heir, the perpetrator of the killing, could still inherit. To analyze this issue, a normative juridical research method is employed. For ease of research, the author presents a case illustration that is not based on real events. The data is collected through literature studies and analyzed qualitatively. The necessary data sources include the Civil Code (KUHPerdata), the Compilation of Islamic Law (KHI), and relevant scholarly journals. This study concludes that the position of A1 as a substitute heir is obstructed from inheriting because they have killed A, based on the provisions of Article 838 of the Civil Code. However, there are specific conditions that could allow A1 to still receive their inheritance rights, considering that the inheritance still belongs to P, not A. One possible approach is for A1 to file a lawsuit in the District Court, requesting the judge to render a fair decision by taking into account factors of justice and the emotional relationship between A1 and P.